Optoelectronic pantography diagnostics of temporomandibular disorders in patients with bruxism - Mehulić, Ketij; Kevilj Gospić, Renata; Dundjer, Alenko; Škrinjarić, Tomislav; Štefančić, Sanja; Vojvodić, Denis; Perinić, Margareta (2009)
Abstract: Temporomandibular disorders (TMD) is a joint term that encompasses a number of clinical symptoms that involve the teeth, masticatory musculature and temporomandibular joints (TMJ). They are a frequent cause of orofacial medical conditions. The aetiology of disorders is complex and individual etiologic factors are not sufficiently defined. Bruxism, in its centric or eccentric form, is becoming a frequent problem for dentists. The purpose of this study is to show factors of the condyle leading in patients with bruxism by optoelectronic pantography, and to establish the possibility of using optoelectronic pantography in the diagnostic procedure of TMD. Patients were selected (N=42), with incomplete sets of teeth, without prosthodontic appliances and with traces and symptoms of TMD. After completing the history questionnaire a clinical check up and plaster cast analysis patients with bruxism were selected (N=22) and without bruxism (N=20). During the study optoelectronic String-condylocomp LR3, Dentron, D-Höchberg (software JAWS 30) was used. This study showed the possibility of applying optoelectronic pantography in TMD diagnostics and compares history, clinical and condylographic parameters in TMD patients with and without bruxism. Optoelectronic pantography enables us, by using relatively easy methods, to determine a more accurate diagnosis, highly important when choosing therapeutic methods and control of the aforementioned disorders
Bibliografija: 42 jed
Sažetak
Keywords: Temporomandibularni zglob -- Temporomandibularni poremećaj -- Bruksizam -- Optoelektronička pantografija -- Dijagnostika